2020
DOI: 10.1016/j.jhep.2020.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Variants in ABCB4 (MDR3) across the spectrum of cholestatic liver diseases in adults

Abstract: The ATP binding cassette subfamily B member 4 (ABCB4) gene on chromosome 7 encodes the ABCB4 protein (alias multidrug resistance protein 3 [MDR3]), a P-glycoprotein in the canalicular membrane of the hepatocytes that acts as a translocator of phospholipids into bile. Several variants in ABCB4 have been shown to cause ABCB4 deficiency, accounting for a disease spectrum ranging from progressive familial cholestasis type 3 to less severe conditions like low phospholipid-associated cholelithiasis, intrahepatic cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 101 publications
1
81
0
Order By: Relevance
“…The latter two findings are consistent with the results of genomewide association studies showing close associations between ABCB4 variants and the risk of developing cirrhosis and/or hepato-biliary malignancies [19,20]. They are also in line with the longterm risk of cirrhosis or cholangitis reported in women with ICP [7,21]. In the present study, most of the cancers diagnosed in index cases or their relatives were cholangiocarcinomas, but a few cases of hepatocellular carcinoma developed on cholestatic or idiopathic cirrhosis were reported in relatives.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The latter two findings are consistent with the results of genomewide association studies showing close associations between ABCB4 variants and the risk of developing cirrhosis and/or hepato-biliary malignancies [19,20]. They are also in line with the longterm risk of cirrhosis or cholangitis reported in women with ICP [7,21]. In the present study, most of the cancers diagnosed in index cases or their relatives were cholangiocarcinomas, but a few cases of hepatocellular carcinoma developed on cholestatic or idiopathic cirrhosis were reported in relatives.…”
Section: Discussionsupporting
confidence: 90%
“…This condition has causally been linked to a defect of phospholipid canalicular secretion into bile leading to impaired solubilization of biliary cholesterol that precipitates in the form of crystals in canaliculi and intrahepatic bile ducts. Germline mutations in the sequence of the ATP-binding cassette subfamily B member 4 (ABCB4) gene, which encodes the phospholipid floppase multi-drug resistance type 3 (MDR3), have been reported in 30% to 50% of patients with this condition [2][3][4][5][6], thus including LPAC syndrome in the different disease manifestations associated with ABCB4 variants [7].…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…This variant is of low frequency in AA (MAF=1.2%) but virtually absent in EA and ASN. ABCB4, also known as multidrug resistance protein 3 (MDR3), is a compelling candidate gene, as it has been previously implicated in cholestasis, gallbladder disease, and adult biliary fibrosis/cirrhosis [40][41][42] . Finally, for a number of variant gene-pairs, the observed effect on NAFLD risk and the impact of gene expression in the liver was consistent with our understanding of the expected effect given what is known about gene function, suggesting possible relevance as therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Dr. Nayagam and his colleagues for their insightful comment on our recently published review on genetic variants in ABCB4 in adult patients with cholestatic liver disease. 1 In fact, the index patient presented in the clinical vignette within this review showed a comparably mild disease course as his homozygous frameshift variant (p.R1256fs*39) would have suggested. He became symptomatic in early adulthood and showed progression of his cholestatic liver disease with portal fibrosis to decompensated liver cirrhosis within almost 2 decades.…”
Section: To the Editormentioning
confidence: 81%